Efficiency of a Monetary and Credit Policy - Nurgazina, A. M. (Journal of Economic Research & Business Administration, 2016)
Analysis of the instruments of the monetary and credit policy is presented in the article. Central banks use these instruments for the purposes of monetary and credit regulation within the economy in order to provide stability, efficiency and growth of the local market. Central banks in their activity choose main priorities of the monetary and credit policy aiming to establish a price stability, an effective level of money supply and circulation, as well as a payment system development. Regulation of the financial system and its participants can be considered as an additional task for the central banks. From one hand, if the world market have positive movements, instruments of the monetary and credit policy issued by the central bank, stimulate and push the economy to the further growth. From other hand, in bad economic environment, these measures support and protect an internal market from a negative influence arising in present or coming in future.